Crystal structure of glutamate dehydrogenase 2, a positively selected novel human enzyme involved in brain biology and cancer pathophysiology. Issue 3 (23rd January 2021) - Dimovasili, Christina; Fadouloglou, Vasiliki E.; Kefala, Aikaterini; Providaki, Mary; Kotsifaki, Dina; Kanavouras, Konstantinos; Sarrou, Iosifina; Plaitakis, Andreas; Zaganas, Ioannis; Kokkinidis, Michael
Abstract: Introduction: Mammalian glutamate dehydrogenase (hGDH1 in human cells) interconverts glutamate to α‐ketoglutarate and ammonia while reducing NAD(P) to NAD(P)H. During primate evolution, humans and great apes have acquired hGDH2, an isoenzyme that underwent rapid evolutionary adaptation concomitantly with brain expansion, thereby acquiring unique catalytic and regulatory properties that permitted its function under conditions inhibitory to its ancestor hGDH1. Although the 3D‐structures of GDHs, including hGDH1, have been determined, attempts to determine the hGDH2 structure were until recently unsuccessful. Comparison of the hGDH1/hGDH2 structures would enable a detailed understanding of their evolutionary differences. This work aimed at the determination of the hGDH2 crystal structure and the analysis of its functional implications. Recombinant hGDH2 was produced in the Spodoptera frugiperda ovarian cell line Sf21, using the Baculovirus expression system. Purification was achieved via a two‐step chromatography procedure. hGDH2 was crystallized, X‐ray diffraction data were collected using synchrotron radiation and the structure was determined by molecular replacement. The hGDH2 structure is reported at a resolution of 2.9 Å. The enzyme adopts a novel semi‐closed conformation, which is an intermediate between known open and closed GDH1 conformations, differing from both. The structure enabled us to dissect previously reported biochemical findings and to structurally interpret the effects of evolutionary amino acid substitutions, including Arg470His, on ADP affinity. In conclusion, our data provide insights into the structural basis of hGDH2 properties, the functional evolution of hGDH isoenzymes, and open new prospects for drug design, especially for cancer therapeutics. Abstract : We present the 3D‐structure of the hGDH2 enzyme, one of the two isoenzymes of human GDH. These two isoenzymes, hGDH1 and hGDH2, are encoded by two evolutionary related genes, GLUD1 and GLUD2, respectively, with the latter evolving from retroposition of the former, less than 23 million years ago. Despite the high degree of sequence and structural similarity between the hGDH isoenzymes, the unique properties of hGDH2 can be explained by the physicochemical properties of amino acid substitutions (including but not limited to Arg443Ser, Gly456Ala and Arg470His), which accumulated in critical positions of its structure after it originated from hGDH1.